Relative pay, effort, and labor supply - Anat Bracha (IZA World of Labor, 2017)
Recent studies show that even irrelevant relative pay information—earnings compared to the past or to others—significantly affects workers' willingness to work (labor supply) and effort. This effect stems mainly from those whose pay compares unfavorably; accordingly, earning less compared to others or less than in the past significantly reduces one's willingness to work and effort exerted on the job. Comparing favorably, however, has mixed effects—with usually no effect on effort, but positive or no effects on labor supply. Understanding when relative pay increases labor supply and effort can thus help firms devise optimal payment structures.
Keywords: J30; 330; relative pay; effort; labor supply; lab experiments; field experiments